Durability of concrete exposed to combined freeze-thaw, sulfate, and acid attacks after two years - Tanyildizi, Harun (Revista de la Construcción. Journal of Construction, 2024)
This study investigated the frost resistance of concrete exposed to sulfate and acid attacks after two years. The cement content was selected as 300 kg/m3, 350 kg/m3, 400 kg/m3, 450 kg/m3, and 500 kg/m3 in this study. 100 mm cubic specimens were prepared for experiments. After the specimens were cured in the water at 20 ± 2 °C for 28 days, they were kept in the laboratory conditions at 20 ± 2 °C for 23 months+2 days. Then, these samples were subjected to freeze-thaw cycles after being exposed to 5% sodium sulfate, 5% magnesium sulfate, 1% sulfuric acid, and 2% sulfuric acid for four days. Thus, the samples were exposed to the four different combined attacks. Lastly, the mechanical properties, weight change, and relative dynamic modulus of elasticity of these specimens were determined. Furthermore, the SEM and EDS analyses were carried out on samples. This study found that the highest compressive strength, the highest ultrasonic pulse velocity, and the lowest weight loss were the samples with 500 kg/m3 cement content subjected to combined freeze-thaw and 1% acid attack.